Customized approach for upfront or delayed resection using radiological criteria in unilateral, nonmetastatic pediatric renal tumors: A prospective study. (16th May 2019) - Qureshi, Sajid S.; Kembhavi, Seema A.; Bhagat, Monica; Kapadia, Tejas; Prasad, Maya; Vora, Tushar; Chinnaswamy, Girish; Ramadwar, Mukta; Laskar, Siddhartha; Khanna, Nehal; Baheti, Akshay; Shah, Sneha; et al.
Abstract: Background: The availability of robust, equivalent data regarding outcomes for upfront or delayed surgery for renal tumors in children leads to a dilemma in selecting the initial treatment. Imaging criteria associated with the probability of rupture or incomplete resection may provide a more objective assessment for customization for the timing of surgery. Procedure: Eighty‐three children with unilateral, nonmetastatic renal tumors were enrolled between January 2012 and April 2018. Upfront nephrectomy was performed in the absence or delayed surgery (after a biopsy and chemotherapy) in the presence of one or more imaging‐based high‐risk features, including perinephric spread or adjacent organ infiltration, tumors crossing the midline, intravascular thrombus, and extensive adenopathy. Post hoc analysis for interobserver concordance for high‐risk imaging features was also performed. Results: The upfront surgery group (19) had predominantly stage I or II diseases (89%) and the histological types were Wilms (13), non‐Wilms (5) renal tumor, and an inflammatory lesion. The delayed surgery group had 60% with stage I or II diseases and the histological types were Wilms (60) and non‐Wilms (4) tumor. In addition, high‐risk pathology was identified in nine patients. Overall, 27 patients with Wilms tumors required radiotherapy and anthracycline because of stage III disease, including one in the immediate surgery group. The event‐free and overall survival (OS) at a median follow‐up of 39 months for Wilms tumor are 88% (95% confidence interval [CI]: 78.5‐94.9%) and 89% (95% CI: 81.4‐96.6%), 85.1% (95% CI: 73.8‐93.4%) and 86.5% (95% CI: 77.4‐95.8%) for the delayed, and 100% event‐free survival as well as OS ( P = .1) in the upfront surgery group. Conclusion: A customized approach pivoted on image‐based high‐risk features facilitates identification of patients with early‐stage renal tumor when the timing of surgery is tailored. Moreover, non‐Wilms tumor and high‐risk pathology are also identified.